Optimal regime of jet fuel water impregnation by ultrasonic dispersion method - Бережний, В. Г.; Туз, М. Д.; Кер'якос, Д. (Proceedings of National Aviation University (archive), 2000)
Analyzed is the efficiency of existing method and devices of jet fuel water impregnation, their advantages and disadvantages. Proposed is a principal scheme of installation and optimal regime of jet fuel water impregnation by ultrasonic dispersion method